Healthy conversation skills: increasing competence and confidence in front-line staff. Issue 3 (19th September 2012) - Black, Christina; Lawrence, Wendy; Cradock, Sue; Ntani, Georgia; Tinati, Tannaze; Jarman, Megan; Begum, Rufia; Inskip, Hazel; Cooper, Cyrus; Barker, Mary; Baird, Janis
Abstract Objective (i) To assess change in confidence in having conversations that support parents with healthy eating and physical activity post-training. (ii) To assess change in staff competence in using 'open discovery' questions (those generally beginning with 'how' and 'what' that help individuals reflect and identify barriers and solutions) post-training. (iii) To examine the relationship between confidence and competence post-training. Design A pre–post evaluation of 'Healthy Conversation Skills', a staff training intervention. Setting Sure Start Children's Centres in Southampton, England. Subjects A total of 145 staff working in Sure Start Children's Centres completed the training, including play workers (43 %) and community development or family support workers (35 %). Results We observed an increase in median confidence rating for having conversations about healthy eating and physical activity (both P < 0·001), and in using 'open discovery' questions (P < 0·001), after staff attended the 'Healthy Conversation Skills' training. We also found a positive relationship between the use of 'open discovery' questions and confidence in having conversations about healthy eating post-training (r = 0·21, P = 0·01), but a non-significant trend was observed for having conversations about physical activity (r = 0·15, P = 0·06). Conclusions The 'Healthy Conversation Skills' training proved effective at increasing the confidence of staff working at Sure Start Children's Centres to have more productive conversations with parents about healthy eating. Wider implementation of these skills may be a useful public health nutrition capacity building strategy to help community workers support families with young children to eat more healthy foods.